Legume isoflavone synthase genes have evolved by whole-genome and local duplications yielding transcriptionally active paralogs. (November 2017) - Narożna, Dorota; Książkiewicz, Michał; Przysiecka, Łucja; Króliczak, Joanna; Wolko, Bogdan; Naganowska, Barbara; Mądrzak, Cezary J.
Highlights: Lupinus angustifolius genome encodes three isoflavone synthase (IFS) genes. IFS genes in legumes have evolved by whole-genome and tandem duplications. The vast majority of legume IFS duplicates maintained transcriptional activity. IFS duplicates experienced strong purifying selection pressure during evolution. Abstract: Isoflavone synthase (IFS) is the key enzyme of isoflavonoid biosynthesis. IFS genes were identified in numerous species, although their evolutionary patterns have not yet been reconstructed. To address this issue, we performed structural and functional genomic analysis. Narrow leafed lupin, Lupinus angustifolius L., was used as a reference species for the genus, because it has the most developed molecular tools available. Nuclear genome BAC library clones carrying IFS homologs were localized by linkage mapping and fluorescence in situ hybridization in three chromosome pairs. Annotation of BAC, scaffold and transcriptome sequences confirmed the presence of three full-length IFS genes in the genome. Microsynteny analysis and Bayesian inference provided clear evidence that IFS genes in legumes have evolved by lineage-specific whole-genome and tandem duplications. Gene expression profiling and RNA-seq data mining showed that the vast majority of legume IFS copies have maintained their transcriptional activity. L. angustifolius IFS homologs exhibited organ-specific expression patterns similar to those observed in other Papilionoideae. Duplicated lupin IFS homologs retained non-negligible levels of substitutions in conserved motifs, putatively due to positive selection acting during early evolution of the genus, before the whole-genome duplication. Strong purifying selection preserved newly arisen IFS duplicates from further nonsynonymous changes.